O14 Frequency and site of clinically unsuspected synovitis on whole-body MRI in juvenile idiopathic arthritis. (26th April 2021) - Choida, Varvara; Ciurtin, Coziana; Bray, Timothy J P; Sen, Debajit; Fisher, Corinne; Leandro, Maria; Hall-Craggs, Margaret A
Abstract: Background/Aims   Magnetic resonance imaging can facilitate the diagnosis of JIA, but is also increasingly used for monitoring disease activity in individual joints. This prospective study aims to measure the frequency of subclinical synovitis on whole-body MRI, in adolescent patients with JIA. Methods   JIA patients were recruited from a tertiary adolescent and young adult rheumatology clinic, between September 2019 and August 2020. All patients were examined by a senior rheumatology registrar, before undergoing a contrast enhanced whole-body MRI scan. Patients were assigned to a clinically active or inactive group, depending on their active joint count (AJC); active patients had AJC≥ 1, while the clinically inactive patients had an AJC =0. The post-contrast, water-only mDixon images were assessed for synovitis by one radiologist, blinded to clinical information. Only joints that were definitely abnormal were counted as synovitic. Eighty-one joints per patient were examined with both methods. The presence of subclinical synovitis in a patient was defined as synovitis in one or more joints on MRI, which were not active clinically. Results   Thirty-two patients aged 15 to 24 were included in the analysis. The patient characteristics and the frequency of subclinical synovitis are summarised in the table. Subclinical synovitis was detected in a similar proportion of JIA patients in both active and inactive groups (46.7% vs. 41.2%, P = 0.76). The most frequent region with subclinical synovitis was the hindfoot, detected in 22% (7/32) of JIA patients and 17.2% (11/64) of hindfoot joints assessed by MRI. The second most common joint with clinically unsuspected inflammation was the knee, found in 19% (6/32) of JIA patients and 14% (9/64) knee joints. Similarly, 16% (5/32) of the adolescent patients had active disease in the hip, ankle or midfoot joints. The frequency of elbow involvement was also considerable, with 12% (7/58) of joints with subclinical synovitis in 14% (4/29) of JIA patients. Conclusion   In conclusion, 43.8% of JIA patients had subclinical synovitis on whole-body MRI scan with no significant difference between the clinically active vs. inactive JIA patients. Large joints were predominantly affected. Further research is required to validate our findings in a larger cohort of JIA patients. Disclosure   V. Choida: None. C. Ciurtin: None. T.J.P. Bray: None. D. Sen: None. C. Fisher: None. M. Leandro: None. M.A. Hall-Craggs: None.